Morphological analysis of Londrina: application of Munizaga’s patterns - Audibert, Esther Encinas (2014)
There are several approaches to city analysis. Urban Morphology focuses on the form of urban elements considering temporal issues. Current research employs the Structural Elements defined by Munizaga’s methodology (1993) and analyzes maps published in 1932, 1934, 1935, 1938, 1949 and 1951 of the first town planned by the Paraná Plantations (CTNP). Compositions with regard to Types and Configuration Patterns were verified. Transformations occurred as from the original plan, with the maintenance of the former structure and the main axes. Initial imprints preserving the primary stratum of the city may be identified. By employing Munizaga’s Urban Structures, the analyses of the maps revealed the beginning of disarticulation of the planned city, back in 1938. These transformations were more evident in 1949. Current research contributes towards the understanding of the genesis, permanence and transformations ofLondrina’s landscape.